2014
DOI: 10.1111/apha.12288
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the activity and expression of protein phosphatase‐1 accompany the differential regulation of NHE3 before and after the onset of hypertension in spontaneously hypertensive rats

Abstract: Collectively, these results support the idea that the lower NHE3 transport activity and higher phosphorylation occurring after the development of hypertension in SHRs are due, at least in part, to reduced PP1-mediated dephosphorylation of NHE3 at serine 552.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Lower levels of phosphorylated NHE3 at the PKA consensus site serine 552 in the proximal tubule has been associated with higher NHE3 transport activity (Crajoinas et al, 2010 , 2014 ; Girardi and Di Sole, 2012 ; Pontes et al, 2015 ; Farah et al, 2016 ). As show in Figures 7A,B , the levels of NHE3 phosphorylation at serine 552 (PS552-NHE3) were much lower in HF than in sham-operated rats (39 ± 4 vs. 100 ± 3%, P < 0.01) (Figures 7A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower levels of phosphorylated NHE3 at the PKA consensus site serine 552 in the proximal tubule has been associated with higher NHE3 transport activity (Crajoinas et al, 2010 , 2014 ; Girardi and Di Sole, 2012 ; Pontes et al, 2015 ; Farah et al, 2016 ). As show in Figures 7A,B , the levels of NHE3 phosphorylation at serine 552 (PS552-NHE3) were much lower in HF than in sham-operated rats (39 ± 4 vs. 100 ± 3%, P < 0.01) (Figures 7A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Harvested hearts from rats were homogenized in a Polymix PX-SR 50 E homogenizer (Kinematica, AG, Switzerland) in ice-cold phosphate buffered saline (PBS) (10 mmol/L phosphate, 140 mmol/L NaCl, pH 7.4), including phosphatase inhibitors (15 mM NaF and 50 mM sodium pyrophosphate) and Halt Protease Inhibitor Cocktail (Thermo Fisher Scientific, Rockford, IL). Renal cortical homogenates were prepared as previously described (Crajoinas et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKA activity was indirectly measured via immunoblotting. Equal amounts (25 g) of plasma membrane protein isolated from rat renal cortices were resolved by SDS-PAGE and analyzed via immunoblotting using a specific antibody that recognizes phosphorylated PKA substrates (16). Visualized bands were digitized with an Image Scanner (GE HealthCare) and quantified with the Scion Image Software package (Scion, Frederick, MD).…”
Section: Methodsmentioning
confidence: 99%
“…The Na + /H + exchanger 3 in the proximal tubules of the kidney has long been implicated in the development of hypertension in spontaneously hypertension in rats (SHRs; Thomas et al, 1988 , 1990 ; Kelly et al, 1997 ; Aldred et al, 2000 ; LaPointe et al, 2002 ; Kemp et al, 2014 , 2016 , 2022 ). Whether NHE3 in the proximal tubules plays any role in hypertension in SHRs remains incompletely understood ( Yip et al, 1998 ; Magyar et al, 2000 ; Panico et al, 2009 ; Crajoinas et al, 2014 ). Early in vivo micropuncture studies suggested that the development of hypertension in young SHRs up to 8 weeks of age involves sodium retention with significantly increased proximal tubule reabsorption (Jv; Thomas et al, 1988 , 1990 ).…”
Section: Nhe3 In the Proximal Tubules Of The Kidney And The Developme...mentioning
confidence: 99%